EVALUATION OF VISUAL EVOKED POTENTIAL (VEP) IN THE OFFSPRING OF TYPE II DIABETIC PARENT(S). - ANITHA A; JANANI R; SUDHARSHINI P (International Journal of Pharma and Bio Sciences, 2015)
Metabolic abnormalities in Diabetes Mellitus can involve ganglionic and preganglionic elements in the entire retina and macular region causing Visual disturbances.Subclinical CNS dysfunctions have been reliably detected by Visual evoked potentials in patients with uncomplicated diabetes and normal brain CT scan. The offspring of diabetic parents have a higher risk of diabetes in future and a possibility of Diabetic retinopathy.This study aims at evaluating visual evoked potential in asymptomatic offspring of diabetic parents.150 individuals in each group(case and controls) were enrolled after Written and informed consent . Institutional ethical Committee approval was obtained., VEP readings were taken using the standard procedure as given by Recommended Standards for Visual Evoked Potential, Guidelines 9B.RESULT;The statistical analysis revealed significant difference in controls and offspring of diabetic parents in terms of P100 latency in both left and right eye (P<0.05).The offspring of diabetic parents may be screened with VEP ,as , prolongation of P100 latency a direct sign of retinal damage and demyelinationcould add the risk to the fact that they may be in a pre-diabetic stage without clinical manifestation,but there may be subclinical optic pathway involvement which mandates active intervention to reduce the co-morbidly associated with Diabetes.